2020
DOI: 10.1051/sicotj/2020028
|View full text |Cite
|
Sign up to set email alerts
|

Survival rate of cemented versus cementless tibial component in primary total knee arthroplasty over 5 years of follow-up: comparative study of 109 prostheses

Abstract: Introduction: Knee osteoarthritis is the main indication for primary total knee arthroplasty (TKA). It is now accepted that cementless implantation of the femoral component provides equivalent results to cemented one, however, the optimal fixation method of the tibial component remains controversial. The purpose of this study was to compare the survivorship of cemented versus cementless tibial baseplate in primary total knee arthroplasty. Materials and methods: We carried out a retrospective, monocentric study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…A number of factors related to component loosening have been described in the literature including but not limited to implant design, type of cement, cement technique, coronal alignment, and polyethylene design. [14][15][16][17][18] Each of these factors are somewhat modifiable and with improvements in technology and technique it is possible loosening due to these causes could be avoided. Van Hamersveld et al demonstrated loosening occurred more often in cementless implants without hydroxyapatite coating or highly porous metal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of factors related to component loosening have been described in the literature including but not limited to implant design, type of cement, cement technique, coronal alignment, and polyethylene design. [14][15][16][17][18] Each of these factors are somewhat modifiable and with improvements in technology and technique it is possible loosening due to these causes could be avoided. Van Hamersveld et al demonstrated loosening occurred more often in cementless implants without hydroxyapatite coating or highly porous metal.…”
Section: Discussionmentioning
confidence: 99%
“…14 However, the use of cement, in general, does not seem to play a role as Pacoret et al demonstrated no difference in tibial component survival rate between cemented and cementless fixation with a minimum 5-year postoperative follow-up. 17 With regard to coronal alignment, conflicting conclusions have been reached. In a study of 1151 knees with an average follow-up of 8 ± 4 years, Lee et al concluded that varus malalignment greater than 3 degrees from neutral mechanical alignment was associated with greater rates of aseptic loosening.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent papers have challenged the superiority of cement. Some show that there are no statistically significant differences in clinical and cost outcomes [8][9][10][11][12][13][14][15][16], while others suggest that cementless TKA achieves greater survivorship and long-term functional recovery [17,18] and lower procedure cost [19]. While cement provides immediate fixation, cementless fixation requires the biologic process of osseous integration to occur, and some reports show higher early rates of subtle radiolucencies, implant migration, aseptic loosening and higher early pain scores in cementless TKA [6,[20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have only recently focused on patient-reported outcomes (PRO) as a valuable tool to assess patient recovery, pain and function following TKA [12-18, 25, 26]. With few exceptions [18,26], most studies have found no statistically significant differences in PROs between cemented and cementless TKA [12][13][14][15][16][17]25]. However, these studies have been focused on the experience of a single surgeon or single institution, with limited generalizability.…”
Section: Introductionmentioning
confidence: 99%
“…Five published articles reported interesting results about knee arthroplasty. Pacoret et al described the survival rate of the tibial component in cementless TKA at a mean follow-up of 8 years, with a minimal follow-up of 5 years [7]. Indeed, it is now accepted that cementless implantation of the femoral component provides equivalent results to cemented one, however, the optimal fixation method of the tibial component remains controversial.…”
mentioning
confidence: 99%